Relationships between acceleration, agility, and jumping ability in female volleyball players - Sahin, H. M. (European Journal of Experimental Biology, 2014)
The aim of this study was to determine the relationships between acceleration, agility, and jumping ability in female volleyball players. A total of 12 female collegiate volleyball players were examined. The mean (SD) age was 20,10=1,197 years, height was 1,74=0,057 m, and weight was 61,30=4,244 kg for the 12 volleyball players. In this study, the T test for agility, acceleration test, and vertical jump test were used. A significant negative correlation existed between vertical jump with acceleration and agility (P<0.01). Vertical jump was highly correlated with acceleration and agility ( -0.799, -0.777, respectively). In conclusion, the present research showed vertical jump performance for collegiate female volleyball players that positively effected acceleration and agility. Also, relationship between jump performance and acceleration, agility in volleyball is very important to produce high force and rapid stretch shortening cycle movements and high-speed whole body movements. Vertical jump performance, working with volleyball teams, need to be able to administer efficient, but relationship between vertical jump and acceleration, agility needs to be determined in longitudinal training investigations. Vertical jump and agility, acceleration development program can be designed with minimal cost and equipment. The results of this investigation show that coaches can utilize agility and acceleration training for vertical jump development.